Chapter 7 — Choosing Suitable Trees for Urban and Suburban Sites: Site Evaluation and Species Selection - Edward F. Gilman; Laura Paterson Sadowski (EDIS)
ENH1057, a 9-page full color fact sheet by Edward F. Gilman and Laura Paterson Sadowski, is part of the Urban Forest Hurricane Recovery Program series. It discusses site evaluation, modification, maintenance practices, desirable tree attributes, and tree selection. Published by the UF Department of Environmental Horticulture, September 2007.